Effect of Calliandra planting pattern on biomass production and nutrient accumulation in planted fallows of southern Cameroon - Nolte, C.; Tiki-Manga, T.; Badjel-Badjel, S.; Gockowski, J.; Hauser, S.; Weise, Stephan F. (Elsevier, 2003)
Shortening of fallow periods due to pressure on land by population growth is a common problem throughout the forest zone of West and Central Africa. Crop yields after short-term fallows with natural vegetation are often low as a consequence of low nutrient availability to crops. Planted tree fallows may offer an alternative to natural fallows for improving short fallow-crop cycles if trees accumulate and therefore retain more nutrients in the system. Calliandra calothyrsus (Meissner) (calliandra) trees (3947 ha−1) were planted at different spatial patterns into 18 farmers’ fields in six villages, covering a wide range of soil and rainfall conditions in the forest zone of Cameroon. After 2 year of fallow calliandra tree fallows had produced between 18.9 and 25.0 Mg ha−1 of above-ground dry matter, significantly more than 14.3 and 17.3 Mg ha−1 of dry matter in 2- and 4–5-year old natural fallows, dominated by Chromolaena odorata. Planting trees in alleys and in equidistant pattern produced more biomass than planting in clusters and around the plot borders. The tree fallows accumulated above-ground on average 225 kg N ha−1, significantly more than 168 kg N ha−1 in natural fallows. Alley-planted trees accumulated more P (19 kg ha−1) than natural fallows (14 kg P ha−1), but no difference in K–Ca–Mg accumulation was found. Between 57 and 65% of the biomass in the tree fallows was stem-wood of calliandra, and 23–27% in branch wood. Nutrients in these components are unavailable for annual crops if not burned. Planting trees in clusters and dense lines around the border reduced the stem-wood mass. The stem-wood of calliandra contained on average 18% of the total fallow N, 21% of the P, 28% of the K, 16% of the Ca, and 14% of the Mg. Export of calliandra stems for firewood would, therefore, lead to substantial nutrient losses from the system.